PENGARUH TINGKAT SUKU BUNGA TERHADAP YIELD TO MATURITY OBLIGASI DENGAN DIMEDIASI INFLASI (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Sri Megawati Elizabeth (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
The aims of this research are to know: (1) The effect of interest rate to yield to maturity,(2) The effect of inflation to yield to maturity, (3) The effect of interest rate to inflation, (4) The effect of interest rate to yield to maturity which mediated by inflation. The population of this research are 137 banking sector bonds . With purposive sampling technique, the sample used in this research are 25 banking sector bonds. The method of analysis used in this research is with path analysis and processed using SPSS. The results showed that the interest rate effect to yield to maturity, the interest rate influence to inflation, inflation does not affec to the yield to maturity, inflation mediates the absolute influence between the interest rate to yield to maturity.